(untitled) (Portuguese Journal of Family Medicine and General Practice, 2008)
The AA present the Balint Group lived «from inside», as groupality. They show the evidence of the relational aspects, as third term, included in the situation (sometimes perceived as problematic). The situation is doubly lived: with the patient (as story of the deeply experienced with him) and then within the group (as paradigmatic memories).They also presented the issues referred throughout the years in a Balint Group. Finally deepen the phenomenon «groupality».